RETHINKING OF LOCAL ELECTION IN THE UNITARY STATE: A STUDY OF INDONESIA’S POLITICS - Siti Mutiah Setiawati (FISIP Universitas Malikussaleh, 2023)
The election is very much associated with democracy. As Indonesia is constitutionally democratic the country is also committed to holding the election regularly. However, as Indonesia is a unitary state, identifying local elections with dmocratization might be questionable. This study was a research-based articl on Indonesia’s politics today. A thorough observation of the local election showed that from the perspectiv of economics, the local election was identical to wasting finansial and time energy. In the long run, it may put the country at risk of disintegration from the standpoint of politics. Due to the weaknesses of a local election, the main question is why the Government institutionalizd local polls. Thus, the result revealed that the local election as a means of recruiting local government leaders was worth dismantling and recommended to be replaced by a tight selection of administrative requirements.Pemilu sangat erat kaitannya dengan demokrasi. Karena Indonesia secara konstitusional demokratis, negara ini juga berkomitmen untuk menyelenggarakan pemilu secara teratur. Namun, karena Indonesia adalah negara kesatuan, mengidentifikasi pemilihan kepala daerah dengan demokratisasi mungkin patut dipertanyakan. Artikel ini merupakan artikel berbasis riset tentang politik Indonesia saat ini. Pengamatan menyeluruh terhadap pilkada menunjukkan bahwa dari segi ekonomi, pilkada identik dengan pemborosan dana dan tenaga waktu. Dalam jangka panjang, hal itu dapat menempatkan negara pada risiko disintegrasi dari sudut pandang politik. Karena kelemahan pilkada, pertanyaan utamanya adalah mengapa Pemerintah melembagakan pilkada. Dengan demikian, hasil penelitian menunjukkan bahwa pilkada sebagai sarana rekruitmen pimpinan pemerintah daerah layak dibongkar dan direkomendasikan untuk diganti dengan seleksi persyaratan administrasi yang ketat.